PRODUKTIVITAS DAN EFISIENSI BEBERAPA PABRIK KAYU LAPIS DI SUMATRA SELATAN DAN KALIMANTAN SELATAN - Akub J Abdurachman (Jurnal Penelitian Hasil Hutan, 1988)
Development of  plywood  industries  should not  be rated from  the  increase of ply mill  number  and  the production aspects alone, but  there is other  indicators  that need be taken  into consideration  such as productivity  and efficiency factors. High productivity and  efficiency   would  bring more profit to  the  company and save the existing  national  resources.In  this report  some  results  of productivity  analysis  is presented based on ratio of actual production   over break even point (BEP) production    level, and efficiency  analysis  is presented   based  on  ration  of actual production  over production capacity  level,   ratio of  output value  over input  value, and added  value of  logs processed  into  plywood  criteria.Based  on  criteria  as  mentioned   above  it  can  be  concluded   that  all six  visited  plymills on  the average have fairly high productivity and efficiency, but utilization rate of existing production capacity is still low.  The average ratio of actual production over BEP production is 2.48  with  range 1.35 3.28  (coefficient   of variation 29 %),  the average ratio of actual production   over production   capacity  is 0.64  with  range 0.25 0.91 (coefficient   of  variation  50  %),  the average ratio of output value over input  value is 1.27 with  range 1.071.38  (coefficient   of  variation  10 %),  while  the average of added value of  logs to plywood  is 70 % with  range 17 % -112  % (coefficient   of  variation  21  %).